Effect of energy adequacy level and hydration status on occupational fatigue in fisherman - Delina Krisnauli Safitri; Nur Fitri Widya Astuti; Ana Islamiyah Syamila (AcTion: Aceh Nutrition Journal, 2025)
Fatigue is a risk factor that can reduce the health status of workers and cause accidents. Fatigue can be caused by inadequate energy and hydration levels. This study aimed to determine the relationship between the level of energy adequacy, hydration status, and work fatigue among fishermen in Puger Wetan Village in February to April 2024. This was a cross-sectional study of 106 fishermen.  The data collected were fisherman’s characteristics, Swedish Occupational Fatigue Index (SOFI), self-urine check card, and 2×24 hour food recall. Data were analyzed using Spearman’s rank correlation test. The results showed that more than half (54,7%) of the fishermen experienced moderate fatigue and mild dehydration (41,5%). In addition, the level of energy adequacy (p < 0,0001; r=-0,449) and hydration status (p= 0,003; r= 0,289) were correlated to occupational fatigue. The conclusion is that there is a significant relationship between energy sufficiency and hydration status to   occupational fatigue among fishermen. Fishermen are expected to focus on consuming a variety of foods with balanced nutrition and sufficient body fluid intake. Future research should explore other factors related to occupational fatigue, such as workload, job stress, shift work, and sleep quality.